METODE PENGELOLAAN SISTEM PEMBELAJARAN PAI DI SEKOLAH SALAFIYAH PONDOK PESANTREN ZADUL MA’AD TALANG JAMBE, PALEMBANG - Astri Lestari; Amelia Cahyani; Muhammad Ridwan Baihaqi; Ami Latifah (UNISAN JURNAL, 2023)
This research aims to describe the method of managing the Pai learning system at the Zadul Ma'ad Talang Jambe Salafiyah Islamic Boarding School, Palembang. This research is classified as qualitative research. The data sources in this research are primary data sources and secondary data sources. Data collection methods include observation, interviews and documentation. This research instrument is the researcher as the key instrument using observation guidelines, interview guidelines and documentation note format. From the results of observations and discussions it can be concluded that the system implemented at the Zadul Ma'ad Islamic Boarding School in Palembang is a combination of religious knowledge and general knowledge. namely educational programs which contain learning about science in general and religious knowledge, social programs which are activities that are more focused on activities related to the surrounding community, and code of ethics programs which contain rules that must be implemented by students. The Zadul Ma'ad Palembang Islamic Boarding School has been accredited and is implementing a further program, where students are provided with the Al-Qur'an, namely memorizing and Hadith, reading Ulama books whose learning method is through Nahwu Shorf.